The Effect of Play Therapy on Hospitalization Anxiety Among Pre-School Children (3-6 Years) - Hermalinda Herman; Deswita; Yanti Puspita Sari (Fakultas Keperawatan Universitas Andalas, 2025)
Anxiety and fear due to being hospitalized are still significant problems in nursing services. One of the nursing actions that can minimize stress due to being hospitalized is by playing. This study was aimed to identify the effect of play therapy on hospitalization anxiety among children. The research design was a Quasi-experimental with a sample size of 27 children aged 3-6 years who were hospitalized at public hospital in Padang. The intervention was playing therapy with three different types of games for three days; each game was held for 20-30 minutes. On the first day, the children played constructively using Lego; on the second day, the children were given pictures and colored pencils, and then the children were asked to color. Meanwhile, on the third day, the children played paper folding. During play activities, children were accompanied by parents. The instrument used was a questionnaire about parents' perceptions of the response to anxiety in children aged 1-6 years. The statistical test used is the t-test. The average score of hospitalization anxiety in children aged 3-6 years before the intervention was 32.22, with a standard deviation of 5.68, the lowest score was 18, and the highest was 43. Hospitalization anxiety in children decreased after the intervention, where the average anxiety score was 22.59 with a standard 6.64 deviation, with the lowest score of 51 and the highest score of 41. The results showed that there were significant differences in anxiety scores before and after play therapy. It can be concluded that play therapy can be considered as supportive therapy to overcome hospitalization anxiety in children.